Local Recurrence of Rectal Cancer After Transanal Total Mesorectal Excision and Risk Factors: A Nationwide Multicenter Cohort Study in Japan - Takeru Matsuda, MD, PhD; Ichiro Takemasa, MD, PhD; Hideki Endo, MD, MPH; Shinichiro Mori, MD, PhD; Suguru Hasegawa, MD, PhD; Koya Hida, MD, PhD; Takuya Tokunaga, MD, PhD; Keitaro Tanaka, MD, PhD; Toshiki Mukai, MD, PhD; Jun Watanabe, MD, PhD; Junichiro Kawamura, MD, PhD; Kei Kimura, MD, PhD; et al. (Annals of Surgery Open)
Objective:. To investigate the oncological outcomes after transanal total mesorectal excision (TaTME) for rectal cancer and risk factors for local recurrence (LR). Background:. A high LR rate with a multifocal pattern early after TaTME has been reported in Norway and the Netherlands, causing controversy over the oncological safety of this technique. Methods:. Twenty-six member institutions of the Japan Society of Laparoscopic Colorectal Surgery participated in this retrospective cohort study. A total of 706 patients with primary rectal cancer who underwent TaTME between January 2012 and December 2019 were included for analysis. The primary endpoint was the cumulative 3-year LR rate. Results:. A total of 253 patients had clinical stage III disease (35.8%) and 91 (12.9%) had stage IV. Intersphincteric resection was performed in 318 patients (45.0%) and abdominoperineal resection in 193 (27.3%). There was 1 urethral injury (0.1%). A positive resection margin (R1) was seen in 42 patients (5.9%). Median follow-up was 3.42 years, and the 2- and 3-year cumulative LR rates were 4.95% (95% confidence interval: 3.50–6.75) and 6.82% (95% confidence interval: 5.08–8.89), respectively. A multifocal pattern was observed in 14 (25%) of 56 patients with LR. Tumor height from the anal verge, pathological T4 disease, pathological stage III/IV, positive perineural invasion, and R1 resection were significant risk factors for LR in multivariable analysis. Conclusions:. In this selected cohort in which intersphincteric resection or abdominoperineal resection was performed in more than half of cases, oncological outcomes were acceptable during a median follow-up of more than 3 years.